Implementation of Management of State-Owned Enterprises for People's Welfare - Gunawan Nachrawi (International Journal of Science and Society, 2022)
Initially State-owned enterprises (BUMN) was the result of the nationalization of ex-foreign (Dutch) companies which were later designated as state companies. Then with Law no. 1 Prp 1969 formed the division of 3 types of forms of State-Owned Enterprises into Service Companies (Perjan), Public Companies (Perum) and Persero. This division was formed in accordance with the duties, functions and mission of the business at that time. Thus the first task of the state by forming business entities is to meet all the needs of society, when these sectors cannot be carried out by the private sector. BUMN as a company that obtains State Equity Participation is intended for a form of business that provides high-quality goods and services so that it has competitiveness in the domestic market or international market, and its main objective is to pursue profits to increase company value. The formulation of the problems discussed are: 1) What is the meaning of people's welfare in the management of BUMN in the perspective of Article 33 of the 1945 Constitution of the Republic of Indonesia? and 2) What are the problems in achieving people's welfare through the management of BUMN? Based on the research results, the authors conclude that the problem of achieving people's welfare through the management of BUMN still has a negative impression on the performance of BUMN operating in various economic sectors. BUMN are accused of being business entities that are inefficient and have low profitability. This condition is strongly influenced by the orientation of the establishment of BUMN, which initially prioritized meeting public needs and improving people's welfare compared to profit (profitability). In order to play their role optimally, BUMN can no longer operate solely to meet public needs, due to demands from the business environment in the globalization era for BUMN management to be more competitive so as to be able to provide public facilities with better quality and prices that are affordable to the people.